Kinetic Instabilities from Ion Beams and Differential Streaming in the Close-Sun Solar Wind: Hybrid Expanding Simulations - Matteini,L; Hellinger,P; Landi,S; Franci,L; Tenerani,A; Velli,M (2022)
Parker Solar Probe observations in the inner heliosphere have demonstrated that non-thermal features in solar wind ion distributions are particularly enhanced and dominant in the close-Sun environment. Proton beams and large differential flows of alpha particles are ubiquitously observed, also in slow, though Alfvénic, streams, qualitatively at odds with typical observations at 1AU, where non-Maxwellian features are usually less apparent in the slow solar wind. All this reinforces the idea, also supported by past Helios and Ulysses explorations, that preferential ion heating and acceleration take place already in the Corona and signatures of the kinetic processes involved are gradually washed out during expansion. To explore further properties of ion differential streaming during expansion, as well as associated kinetic instabilities and their possible role in plasma heating, we perform expanding box hybrid simulations of a multi-species solar wind composed by proton core, beam and alpha particles, focussing on the role of wave-particle interactions in shaping distribution functions and controlling relative drifts. Radial trends and typical distributions found in simulations are then compared with PSP and Solar Orbiter observations in the inner Heliosphere.